Effects of isothermal treatment on microstructure and scratch test behavior of plasma sprayed zirconia coatings - Veloso,Guilherme (2004)
The increase of the petroleum cost in the last decades revitalized the interest for lighter and more economic vehicles. Simultaneously, the demand for safe and unpolluted transports grows. The application of thermal barriers coatings (TBC) on combustion chamber and on flat surface of pistons reduces the thermal losses of the engines, resulting in higher temperatures in the combustion chamber. This fact contributes to the improvement of the thermal efficiency (performance) and for the reduction of incomplete combustion. Supported on these initial ideas, thermal barriers coatings constituted by CaO partially stabilized zirconia were produced and their microstructure examined. This coating still presents some drawbacks associated with thermal stresses and permeability to oxidizing gases, which will, eventually, lead to failure of the TBC by spallation. The failure may, in general, be associated to one of three factors: oxide growth at the ceramic-metal interface, formed during thermal cycling; stress build-up due to thermal cycling; and metal-oxide interface segregation, mainly of S. However, it is also relevant to understand the behavior of TBC's under isothermal oxidation. Therefore, this paper investigates the effect of oxidation on the adherence of thermal sprayed coatings. The adherence was measured by linear scratching tests, widely used for thin coatings. Plasma sprayed calcia partially stabilized zirconia was used as TBC and Ni-5%Al as bond coat, with Al substrates. Coated samples were submitted to heat treatments at 500 °C, for 50 h. The microstructures were examined by optical light microscopy, X-ray diffraction, profilometry and SEM.